Fuzzy Bounds: Doing Ethnography at the Limits of the Network and Animal Metaphor - Hansen, Paul (Humanimalia, 2021)
Working on topics where the object of study routinely transgresses what are assumed to be the normative physical and affective boundaries of non-human and human, the concept of “network” and the marker “animal” have proven to be both essential and problematic.  They are especially problematic when one conducts research that is largely rooted in anthropological ethnography; a mode of inquiry dependent not only upon the observation of lives, but on long-term participation in and with those lives. In short, to do anthropological ethnography is it is to live it and to focus on the micro level of interaction first and foremost. This paper argues for the utility of conceptualizing the historical and particular over the timeless and bracketed; re-thinking networks as Ingoldian “meshworks” and not referring to agents or “actants” by abstract categories but through accounting for their specific, historically situated and developed capacities, embodiments and potentials.